2021
DOI: 10.1134/s1061830921100107
|View full text |Cite
|
Sign up to set email alerts
|

A Microwave Coaxial Sensor for Non-Destructive Detection and Analysis of Cracked Teeth

Abstract: A new approach for the detection of cracks in a tooth is presented using a microwave coaxial sensor. In the test, the probe tip is in close contact with the tooth surface, and the fringe electromagnetic fields out of the probe aperture interact with the tooth material. The presence of any crack affects the effective permittivity, causing changes in the signal energy received. Cracks in two representative teeth are evaluated, and they cannot be readily identified in X-ray images. Low signal power was applied du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Li et al [26] used an open coaxial line probe to detect cracks in two teeth over 1-40 GHz. One tooth was extracted due to splitting, and two cracks were barely visible when the two split parts were held together.…”
Section: Reflection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al [26] used an open coaxial line probe to detect cracks in two teeth over 1-40 GHz. One tooth was extracted due to splitting, and two cracks were barely visible when the two split parts were held together.…”
Section: Reflection Methodsmentioning
confidence: 99%
“…2, two cases are compared: one with the coupling liquid only (a mixture of glycerine and water, case A) and the other one with the liquid between the probe and the tooth (case B). Glycerine was chosen, [24] 10 GHz: 7.00-j0.29 (enamel) 6.65-j0.74 (dentin) Enamel [25] 0.1-8.5 GHz Not available 2.4-4.6 with an average of 4.0 Enamel [26] 1-20 GHz as the mixture of glycerine and water did not evaporate at room temperature. The intersection point of the two permittivity spectra indicates a more accurate permittivity value of the tooth at a specific frequency, ie.…”
Section: Permittivity Measurementmentioning
confidence: 99%
“…The type of preservative solution used in the study and its possible contribution to the measured dielectric properties have not been reported. Studies conducted by Meaney et al [ 41 ] and Li et al [ 42 ] also applied the OECP technique to characterize ex vivo teeth, but for different dental purposes. For the purpose of biodosimetry, Meaney et al [ 41 ] compared the relative permittivity of the enamel of five incisor and dental resin samples in the frequency range from 0.1 to 8.5 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported that given the irregular tooth surface, the measurement results contained inevitable air contributions, which was responsible for adding variability to the measurements. Finally, Li et al [ 42 ] applied OECP with a small aperture for the detection of cracked teeth between 1 and 20 GHz. Although measurements of dielectric properties conducted at multiple locations on the permanent molar crown showed consistency, the authors also assumed the presence of small air gaps between the probe tip and the tooth surface.…”
Section: Introductionmentioning
confidence: 99%